The Time Hop Coffee Shop [large type] - Patrick, Phaedra (Thorndike Press large print dynamic drama., 2025)
"Greta Perks was once the shining star of the iconic Maple Gold coffee commercials, the quintessential TV wife and mom. Now fame has faded, her marriage is on the rocks, her teenage daughter has becomedistant, and Greta's once-glittering career feels like a distant memory. When Greta stumbles upon a mysterious coffee shop serving a magical brew, she wishes for the perfect life in those past Maple Gold commercials. Next thing she knows, Greta wakes in the idyllic make-believe town of Mapleville, where the sun always shines and the aroma of freshly brewed coffee and second chances fill the air. Given the opportunity to live the life she dreamed, Greta is determined to rewrite her own script. But can life ever be like a coffee commercial? And what will happen when Greta has to choose between perfection and real life?"--